Checklist of Library Building Design Considerations. - Sannwald, William W. (Chicago : American Library Association, 2001)
From e-readers to cameras and audio recorders to the iPad, Jason provides insight into what these devices can do, how much they cost, and how librarians can use them to enhance their facilities and service.
Intro -- CONTENTS -- PREFACE -- 1 Building and Planning Architecture -- 2 Library Site Selection -- 3 General Exterior Considerations -- 4 Interior Organization of Library Buildings -- 5 Compliance with ADA Accessibility Guidelines -- 6 Telecommunications, Electrical, and Miscellaneous Equipment -- 7 Interior Design and Finishes -- 8 Book Stacks and Shelving -- 9 Building Systems -- 10 Safety and Security -- 11 Maintenance of Library Building Property -- 12 Building Occupancy and Post-Occupancy Evaluation -- 13 Groundbreaking and Dedication Ceremonies -- BIBLIOGRAPHY.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Library architecture -- United States; Architecture -- United States; Electronic books